The Determinants of U.S. Foreign Production: Unions, Monopoly Power, and Comparative Advantage - Thomas Karier (Levy Economics Institute of Bard College, 1990)
Based on an analysis of industry by region data the author finds little evidence that U.S. unions have been a significant factor in the decision of U.S. firms to produce abroad. Additional evidence suggests that U.S. foreign production may have had a negligible effect on the domestic unionization rate. Corresponding with previous research, the results do indicate that comparative advantage, monopoly power, and foreign tariffs are important determinants of U.S. foreign production.
Keywords: 330